Purpose of Implementing Progressive Law against Criminal Offenders in Order to Provide Legal Certainty and Legal Benefits - Harahap, Muhammad Rafandi; Tanjung, Andry Syafrial (Journal of Progressive Law and Legal Studies, 2024)
The implementation of Progressive Law Enforcement is motivated by the desire to avoid negative effects on the ineffectiveness of the criminal justice system in accommodating criminal cases so that the law enforcement process does not continue through the courts. This writing uses descriptive legal research, in which the author uses a normative juridical research type using the Library Research data collection method. This research aims to find out the philosophical basis of Progressive Law in providing legal certainty and legal benefits and the application of Progressive Law by the National Police in increasing the resolution of criminal cases. Based on the research and discussion results, a picture is obtained that law is the rules and guidelines that regulate life in society to create peace and order. Progressive legal ideas occupy a separate legal position. Various groups in handling legal cases, especially in the country, emphasize the preposition of Progressive Legal theory. Especially emphasizing the element of benefit in the form of human peace in society, nation, and state, the implementation of progressive law as an effort to improve the resolution of criminal cases requires that police investigators be able to carry out their duties and authority professionally, accountably and morally so that progressive law enforcement can be in line with legal objectives. It provides legal certainty, legal benefits, and a sense of justice.